Daemons of the shadow realm. 7 - Arakawa, Hiromu, 1973- (Daemons of the shadow realm, 2025)
"All Yuru wants is to live a normal life with his family, but the world has other plans. At the warehouse district, Right and Left continue to duel Ivan while Gonzo and his entourage make quick work of Hayato Shingo's goons. Back at the Kagemori manor, a traitor falls into a deadly trap set by Jin and Gabby. Elsewhere in the city, Asa follows a familiar distress signal, only to find herself face to face with her imposter!" --